Synergy in Building an Islamic Generation: Strengthening Arabic Language Proficiency through the Gombak Utara Learning Center, Kuala Lumpur, Malaysia - Nurul Latifatul Inayati; Mohammad Zakki Azani; Yeti Dahliana; Mujazin Mujazin; Muh. Nur Rochim Maksum; Abil Fida Muhammad Qois Al Hadi; Fadhilla Nangroe Anggraini; Fadhia Ananda; Ellynia Eva Kusuma Dewi; Bella Misbahati Putri; Habibi Fadzlurrahman; Eka Nur Mistiawati (Journal of Community Development, 2025)
The purpose of this community service program is to improve Arabic language skills while strengthening Islamic values among Indonesian migrant children at Sanggar Bimbingan Gombak Utara, Kuala Lumpur, Malaysia. This program was designed to address the problems of low Arabic literacy, limited teaching methods, and weak understanding of Al-Islam and Kemuhammadiyahan (AIK) among diaspora children. Through this initiative, it is expected to foster a young generation with basic Arabic proficiency, strong religious understanding, and confidence in maintaining their Islamic identity within a multicultural environment. The implementation method applied a participatory approach consisting of identification, planning, implementation, evaluation, and reflection stages. Several learning strategies were employed, including Joyful Learning Arabic, Al-Lughah wa Al-Hayah, Pelita Hikmah, Quiz Cahaya Iman, and Sanggar Qur’an. The activities were conducted interactively, involving lecturers, students, local teachers, and PRIM Malaysia to ensure program sustainability. The results show significant improvements both academically and socio-spiritually. Academically, children’s vocabulary mastery, simple conversation skills, and Qur’anic recitation with tajwid improved based on pre-test and post-test results. Socially, the program fostered greater self-confidence, active participation, and a stronger sense of community. Spiritually, the internalization of Islamic values was reflected in children’s daily attitudes and behavior. The program also produced simple teaching modules, online mentoring, and collaborative networks to support sustainability. Thus, this initiative not only addressed short-term needs but also built a relevant, sustainable learning ecosystem that can be replicated in other diaspora communities..